Formulation of choline chloride/ascorbic acid natural deep eutectic solvent: Characterization, solubilization capacity and antioxidant property - Chan, Stephanie; Ling, Jordy; Chan, Yen San; Nandong, Jobrun; Ho, B.K. (Elsevier, 2020)
In the present study, natural deep eutectic solvent composed of choline chloride and ascorbic acid (CHCL/AA NADES) was formulated for enhancing the solubility and antioxidant properties of antioxidant extracts from fruit wastes of Mangifera pajang. The solubilities of Mangifera pajang's antioxidant extracts in water and CHCL/AA NADES at different water contents (0–50 wt%) were investigated. It was observed that the antioxidant extracts were most soluble in the CHCL/AA NADES with 10 wt% of water, and the concentration of antioxidant was found to be approximately 15% and 4% as compared to water and pure CHCL/AA NADES, respectively. The positive effect of water on NADES can be related to the reduced viscosity of NADES, where the viscosity decreased up to 74% upon addition of water. Aside from that, all the tested CHCL/AA NADES enhanced the antioxidant capacity of antioxidant extracts by 1.3–14.64% compared to the antioxidant extracts in water. This finding highlights the role of CHCL/AA NADES as an antioxidant capacity enhancer. Noteworthy, the antioxidant extracts solubilized in the CHCL/AA NADES system formed a nano-scale cluster structure, as depicted by the TEM image, suggesting that the CHCL/AA NADES could potentially use in nanoformulation that provides protection to the antioxidant extracts.